Thiamine responsive pulmonary hypertension: case series - Venkat, Cuddapah Gaurav; Pujitha, Vallivedu Chennakesavulu; Channawar, Kanchan S.; Vasavi, Vadde (International Journal of Contemporary Pediatrics, 2021)
Pulmonary hypertension (PH) is most commonly related either to a cardiac or a pulmonary cause. But less commonly various hematological, hepatic, genetic causes are also associated. Infantile PH due to vitamin deficiencies is very rare though few cases with thiamine deficiencies causing PH have been reported lately. Lack of awareness and late recognition of thiamine deficiency may result in high mortality. A high index of suspicion is required for early diagnosis and management to decrease the severity and morbidity and thereby preventing long term implications on neurological development. Here, we described three cases of infants admitted to Kamineni academy of medical sciences diagnosed with PH who responded dramatically to thiamine supplements. The lack of rapid diagnostic capacity and the severe outcome of thiamine deficiency justify the use of a therapeutic thiamine challenge in cases with high clinical suspicion. Increased awareness about thiamine deficiency and low threshold for thiamine use should guide clinicians in their practice.